Regional aspects of the implementation of social policy on the example of the Рavlodar region (Journal of Economic Research & Business Administration, 2023)
The key function of the state and the main priority of its internal policy is the implementation of social policy, which includes a system of measures implemented by the state in the field of social security of the population and its social protection. The focus of social policy on improving the quality of living of certain groups of the population largely determines the relevance of the problem of financial support of the social system, increasing importance of the financial mechanism.Objective: to consider the main aspects and key characteristics of the state's social policy and the specifics of its implementation at the regional level; to identify the main ways of optimization aimed at improving its effectiveness.Achieving this goal required, firstly, systematization and analysis of the main theoretical aspects that reveal the content, directions of formation and implementation of social policy. Secondly, the definition of the institutional basis for the formation and implementation of social policy. Thirdly, the analysis of the effectiveness of mechanisms for the implementation of social policy at the regional level. Fourth, to assess the socio-economic conditions for the implementation of social policy in the Pavlodar region.The article is based on a comprehensive approach to analyzing the interrelationships of social structure and social policy, taking into account regional aspects. The specifics of the peculiarities of the regions in the formation and implementation of the state social policy were determined..The article notes that the objects of social policy, as a multidimensional and complex process, are the social sphere and social relations based on interaction between social groups and layers of society. The main goal of social policy is the welfare of citizens, their social protection and social development.Keywords: social policy, social services, social development, social protection of the population, income of the population, region